Methicillin-resistant Staphylococcus aureus epidemiology and control in Belgian hospitals, 1991 to 1995. Groupement pour le Dépistage, l'Etude et la Prévention des Infections Hospitalières. - Struelens, M J; Ronveaux, O; Jans, B; Mertens, R (Infect Control Hosp Epidemiol, 1996)
OBJECTIVES: To describe the Belgian methicillin-resistant Staphylococcus aureus (MRSA) surveillance network, the evolution of methods used in Belgian hospitals for MRSA detection and control, and MRSA incidence from 1994 to 1995. DESIGN, SETTING, AND PARTICIPANTS: Questionnaire surveys; infection control physicians from acute-care hospitals in Belgium. INTERVENTION: Publication of national guidelines for MRSA control in 1993. RESULTS: The participation rate in surveys ranged from 42% to 57% of hospitals. In 1995, 88% of participants detected MRSA strains by disk diffusion tests, with little improvement in standardization since 1991. More centers employed the oxacillin agar screen method (27%), automated systems (29%), or a combination of methods (29%) than in 1991 (P < .005). Between 1991 and 1995, the proportion of hospitals reporting MRSA control measures increased from 68% to 95% (P < .01). Practices that were used increasingly included patient placement in private room (from 50% to 93%, P < .01) and hand decontamination with antiseptic (from 43% to 87%, P < .01). The proportion of centers that reported screening MRSA carriers and treating them topically increased two- and threefold, respectively (P < .05). Surveillance data from 1994 to 1995 showed that MRSA represented a mean of 21.3% of S aureus clinical isolates (range, 1.6% to 62.4%). The median incidence of nosocomial MRSA acquisition was 2.8 per 1,000 admissions, with a wide range (0 to 13.7 per 1,000 admissions) across hospitals of all sizes. The median incidence decreased over the first three semesters of surveillance in hospitals with continuous participation. CONCLUSION: MRSA detection and control measures have improved in Belgian hospitals after publication of national guidelines. However, MRSA incidence rates show the persistence of nosocomial transmission, with large variations between centers. The national MRSA surveillance network should indicate whether control efforts eventually will curb the problem.
Keywords: Belgium; Cross Infection; Humans; Infection Control; Methicillin Resistance; Staphylococcal Infections; Staphylococcus aureus